Kajian Karakteristik dan Potensi Aktivitas Antioksidan Teh Daun Beluntas (Pluchea indica L.) dengan Penyertaan Jahe sebagai Minuman Fungsional - Hakim, Ahmad Luqman; Syska, Kavadya; Ropiudin, Ropiudin; Nurhayati, Asti Dewi; Susanto, Andri; Aulia, Risfa; Insani, Choerul; Estiningrum, Diyah Palupi; Istiqomah, Kholifatun; Maskuri, Khasan; Ayuningtyas, Syella Aditya; Najib, Akmal Auladi; Subekti, Ilyas; Qodriyah, Laelatul; Wahdah, Fatimah; Alfiana, Yulia Eva; Khirnika, Asvi; Pranoto, Restu Aji Saripwijaya (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2024)
This research aimed to 1) Determine the characteristics and antioxidant activity of Beluntas Tea with the addition of smashed ginger as a functional beverage; 2) Identify the best formulation for Beluntas tea with ginger as a functional beverage. This research utilized a Completely Randomized Design with two factors: Beluntas tea leaves and smashed ginger with three treatments. The treatments for Beluntas leaves consisted of 70%, 50%, and 30% (w/w). Meanwhile, the treatments for smashed ginger were 30%, 50%, and 70% (w/w). Data were analyzed using ANOVA, and if there were significantly different treatment effects, the Duncan 5% test was applied. Based on the analysis, the treatment with the highest pH value was B3J3 with a value of 7.17. The highest antioxidant value was found in treatment B2J3 with a value of 3.21%, with a Beluntas tea leaves to smashed ginger weight ratio of 1:1.4 g/g. The highest tannin content was observed in treatment B1J1 with a value of 21.85%. The highest yield was obtained from treatment B2J1 with a value of 0.96%. The best treatment based on organoleptic tests was treatment B2J2 with a value of 2.84, which was preferred over the other treatments.